Electronic properties of single-layer tungsten disulfide on epitaxial graphene on silicon carbide. Issue 42 (23rd October 2017) - Forti, Stiven; Rossi, Antonio; Büch, Holger; Cavallucci, Tommaso; Bisio, Francesco; Sala, Alessandro; Menteş, Tevfik Onur; Locatelli, Andrea; Magnozzi, Michele; Canepa, Maurizio; Müller, Kathrin; Link, Stefan; et al.
Abstract : This work reports an electronic and micro-structural study of an appealing system for optoelectronics: tungsten disulphide (WS2 ) on epitaxial graphene (EG) on SiC(0001). Abstract : This work reports an electronic and micro-structural study of an appealing system for optoelectronics: tungsten disulfide (WS2 ) on epitaxial graphene (EG) on SiC(0001). The WS2 is grown via chemical vapor deposition (CVD) onto the EG. Low-energy electron diffraction (LEED) measurements assign the zero-degree orientation as the preferential azimuthal alignment for WS2 /EG. The valence-band (VB) structure emerging from this alignment is investigated by means of photoelectron spectroscopy measurements, with both high space and energy resolution. We find that the spin–orbit splitting of monolayer WS2 on graphene is of 462 meV, larger than what is reported to date for other substrates. We determine the value of the work function for the WS2 /EG to be 4.5 ± 0.1 eV. A large shift of the WS2 VB maximum is observed as well, due to the lowering of the WS2 work function caused by the donor-like interfacial states of EG. Density functional theory (DFT) calculations carried out on a coincidence supercell confirm the experimental band structure to an excellent degree. X-ray photoemission electron microscopy (XPEEM) measurements performed on single WS2 crystals confirm the van der Waals nature of the interface coupling between the two layers. In virtue of its band alignment and large spin–orbit splitting, this system gains strong appeal for optical spin-injection experiments and opto-spintronic applications in general.